Evaluating the Kernighan-Lin heuristic for hardware/software partitioning - Mann, Zoltán Ádám; Orbán, András; Farkas, Viktor (Zielona Góra: Uniwersytet Zielonogórski)
In recent years, several heuristics have been proposed for the hardware/software partitioning problem. One of the most promising directions is the adaptation of the Kernighan-Lin algorithm. The Kernighan-Lin heuristic was originally developed for circuit partitioning, but it has been adapted to other domains as well.
Keywords: Kernighan/Lin heuristic; Fiduccia/Mattheyses heuristic; hardware/software partitioning; hardware/software codesign